PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA TEMA 1 BENDA-BENDA DI LINGKUNGAN SEKITAR SUBTEMA 1 WUJUD BENDA DAN CIRINYA DI KELAS V SDN RANCASAWO 1 - Mumin Saud, Abdul; Sri Rahayu, Elis (STKIP Subang, 2017)
This study aims to improve the activity and student learning outcomes by using the model of Discovery Learning on the theme of objects in the environment around the subtema of the form of objects and characteristics. . This research was conducted in class V SDN Rancasawo 01 and the background of students who showed less activity in the learning process and the result of learning that still have not reached the minimum mastery criteria, this is because teachers often use lecture methods that tend to monoton and have not used the model of Discovery Learning. Assessment used in this research is pretest and post test technique to know student learning result, activity assessment and observation sheet to know teacher and student attitudes during learning process. The results showed an increase in the mean of the activity assessment and the results of the learning test. In the activity assessment the average value of cycle 1 is 58.57, while cycle 2 reaches 80% and cycle 3 reaches 90%. The learning outcomes in cycle 1 average value that is equal to 54,61%, in cycle 2 reach 80,38% and result learn at cycle 3 reach 91,79%. This shows that the use of discovery learning model can improve the activity and learning outcomes of students on the theme of objects in the surroundings around the subtheme of objects and the characteristics of class V SDN Rancasawo 01. Thus, the use of the model of Discovery Learning can be used as one of the learning models to be applied to Thematic learning with other themes and subthemes.